SMU adds another sustainable building to its city campus - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
Singapore Management University (SMU) today officially launched a new seven-storey multi-use building that adds over 12,700 square metres of teaching, learning, research and faculty space to its footprint. The ceremony was officiated by Guest-of-Honour Mr Heng Swee Keat, Deputy Prime Minister and Coordinating Minister for Economic Policies, in the presence of 250 guests and SMU faculty, staff, students and alumni.